Aplysina aerophoba (Nardo, 1833) (Porifera, Demospongiae): an unexpected miniaturised growth form from the tidal zone of Mediterranean caves: morphology and DNA barcoding. Issue 1 (1st January 2020) - Costa, G.; Violi, B.; Bavestrello, G.; Pansini, M.; Bertolino, M.
Abstract: In the Mediterranean Sea, the two sponges of the genus Aplysina ( A. aerophoba and A. cavernicola ) are identified on the basis of their external morphology and the environment in which they live. During a research program on the sponge fauna in semi-submerged caves of the Italian coasts, we have sampled an abundant very small yellow sponge, often living in the tidal zone, which were attributed to the genus Aplysina . Failing to assign the samples to a species through classical taxonomic methodologies (growth form and skeleton arrangement) and for the particular environment where this sponge lives, we have decided to use the COI analysis to solve the taxonomic problem offered by these miniaturized specimens. The analysis indicated that, in spite of the morphological differences, they belong to A. aerophoba . During old detailed surveys, conducted in the '60 years in some of the studied caves, this species was not recorded. It is possible that its abundant presence is related to the modifications occurred in the Mediterranean sponge communities occurred in the last decades in relation to global warming.